Women’s Online Driver! Flexibility and Work Environment to Job Satisfaction: Moderation Effect of General Anxiety Disorder - Maroddah, Rozanatul; Eko Pujianto, Wahyu (Martabat: Jurnal Perempuan dan Anak, 2023)
Online drivers are one of the alternative jobs in the informal sector. In the development of women's increasingly active roles, work flexibility and work environment are key factors that influence the job satisfaction of female drivers. The purpose of this study was to analyze the relationship between work flexibility, work environment, and job satisfaction in female drivers. In addition, this study was conducted to examine whether generalized anxiety disorder can moderate this relationship. The method used is quantitative method, using purposive sampling technique based on 99 female drivers. Data collection was done through online questionnaire distribution (Facebook, Instagram, WhatsApp). The results of this study indicate that flexibility has no significant effect on job satisfaction, and the work environment has a significant effect on job satisfaction. Generalized anxiety disorder has no significant impact on job satisfaction. While as a moderating variable, generalized anxiety disorder weakens the relationship between flexibility and work environment on job satisfaction.